Proceedings of the International Conference on Educational Sciences and Teacher Profession (ICETeP 2018) 2019
DOI: 10.2991/icetep-18.2019.71
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Jumping Task and Collaborative Activity on Enhancement of Student Critical Thinking Ability

Abstract: The development of critical thinking ability needs attention in learning. To achieve this goal, collaborative activities must create in learning. The teacher can giving students a jumping task as a stimulated to collaborative activities. This study aims to examine in depth the results of learning observations for subjects in Social Sciences, Natural Sciences, and English in two partner schools of the Teacher Training and Education Faculty -University of Lampung, Indonesia. The study was conduct on 33 Senior hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The results showed that jumping tasks could bring out students' critical thinking process based on IDEALS steps. The results of this study are strengthened by and Noer (2019), stating that jumping tasks as problem-solving can be used to enhance students' critical thinking process. This study showed that most subjects had difficulty in doing jumping tasks.…”
Section: The Critical Thinking Process Of Abstract Random Subjects (Ar)mentioning
confidence: 68%
See 1 more Smart Citation
“…The results showed that jumping tasks could bring out students' critical thinking process based on IDEALS steps. The results of this study are strengthened by and Noer (2019), stating that jumping tasks as problem-solving can be used to enhance students' critical thinking process. This study showed that most subjects had difficulty in doing jumping tasks.…”
Section: The Critical Thinking Process Of Abstract Random Subjects (Ar)mentioning
confidence: 68%
“…Furthermore, research by Kurniati and Trapsilasiwi (2017) described the collaboration process in the application of collaborative learning by jumping tasks in a mathematics classroom. Furthermore, Noer, Hasnunidah, and Abdurrahman (2019) examined the effect of collaborative learning and jumping tasks on students' critical thinking skills. In contrast to those studies, this study focused on describing Year 7 students' critical thinking process in solving jumping tasks based on Gregorc's thinking style on the algebraic subject.…”
Section: Introductionmentioning
confidence: 99%
“…Most students agreed that the sharing and jumping task reduced the difficulty of comprehending the lesson (Figure 13) and improved their comprehension of the topic (Figure 14). The success of implementing Sharing and Jumping tasks in learning has been widely reported in various fields of study, such as Science (Fatimah et al, 2018;Ogegbo et al, 2019), Mathematics (Gustiningsi et al, 2022), and other lessons (Noer et al, 2019;Shi & Cheng, 2021). Increased student problem-solving skills contributed to this accomplishment (Hobri et al, 2020).…”
Section: Student' Response To the Tasksmentioning
confidence: 99%